Pendugaan Area Kecil Angka Partisipasi Kasar Perguruan Tinggi di Indonesia Menggunakan Model Subarea Twofold dengan Pendekatan Hierarchical Bayes - Reyhan Saadi; Azka Ubaidillah (Seminar Nasional Official Statistics, 2022)
Gross Enrolment Rate of higher education (APK PT) is an indicator that can be used to measure the achievement of the SDGs program in the context of education. Unfortunately, this data with good quality can only be presented up to the provincial level because the number of SUSENAS samples is designed to be only sufficient to present data up to the provincial level. These limitations makes it difficult to provide good quality district APK PT data. In fact, in formulating policies, APK-PT data is needed with availability to the level of small areas such as districts as a comparison. The SAE method can be an alternative way to improve the quality of the APK-PT estimation results at the small area level. Along with the increasing need for small area data, currently an SAE model has been developed with ability to estimate at two levels of a small area, namely twofold subarea model. Seeing this opportunity, researchers are interested in estimating the APK-PT of districts and provinces in Indonesia with the twofold subarea model using the HB approach. The estimation results shows that this model is able to produce better APK-PT estimates in both regency and province level.